2016
DOI: 10.1111/gfs.12228
|View full text |Cite
|
Sign up to set email alerts
|

Grazing behaviour, intake and performance of dairy ewes with restricted access time to berseem clover (Trifolium alexandrinum L.) pasture

Abstract: The effects of restricted access time to pasture (2, 4 or 6 h d À1 ; 2H, 4H or 6H) on ingestive behaviour and performance were assessed on four occasions per target grazing day (D1, initial day; D4, intermediate day; and D7, final day) in dairy ewes rotationally grazing berseem clover with a 7-day grazing period and a 21-day recovery period. A randomized block design with two replicates per treatment was used. All ewes were supplemented daily with 700 g per head of concentrates and 700 g per head of ryegrass-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
2
15
1
Order By: Relevance
“…Allocation of time at pasture can affect animal performance or grazing behaviour of animals entering restrictedly to an improved pasture (Gregorini et al 2009;Molle et al 2017). The live weight ADG of animals with access to oats was greater than that of animals in the control group at the end of Phase I (Figure 2); however, this response was related with the frequency of oats access within a week´s duration, being greater for E than for MthF animals ( Table III).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allocation of time at pasture can affect animal performance or grazing behaviour of animals entering restrictedly to an improved pasture (Gregorini et al 2009;Molle et al 2017). The live weight ADG of animals with access to oats was greater than that of animals in the control group at the end of Phase I (Figure 2); however, this response was related with the frequency of oats access within a week´s duration, being greater for E than for MthF animals ( Table III).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that altering the time allocation at pasture when restricting grazing time, affects animal grazing behaviour and performance (Gregorini et al 2009;Molle et al 2017). However, Soca et al (2014) found that restricting daily grazing access to improved pastures on dairy cows had a significant effect on total grazing time, but in this case, no significant effect was found on herbage dry matter intake nor on animal performance.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, lactating ewes and goats usually have NDFI levels markedly higher than the value of 1.1% suggested for cattle. As an example, Molle et al (2014 , 2016 ) reported NDFI levels of 2.28% of BW for 42-kg lactating ewes, while Olsen (2016) , summarizing the values of six experiments carried out on Nordic lactating ewes, found a value of 1.76% of BW for 92-kg ewes. Similarly, the intake level of NDF during pregnancy in ewes is much higher (around 1% of BW) than that usually observed in cows (around 0.6%) (A. Cannas, personal communication).…”
Section: Implication Of Nutritional Differences Among Domestic Ruminamentioning
confidence: 99%
“…Equation 1 assumed the maximum dietary concentrations of NDF to avoid rumen fill restriction on DMI were calculated for sheep of different mature BW and milk production. These values were evaluated by using the 50 individual measurements of ad libitum DMI, diet composition, and milk production of lactating ewes ( Molle et al, 2014 , 2016 ). There was a fairly close agreement between predicted and observed dietary NDF concentrations (root of the mean squared prediction error was 5.0% NDF, the concordance correlation coefficient was 0.64, and r 2 = 0.57) and a very close agreement between predicted and observed DMI (root of the mean squared prediction error was 0.11 kg/d, concordance correlation coefficient was 0.94, r 2 = 0.94).…”
Section: Implication Of Nutritional Differences Among Domestic Ruminamentioning
confidence: 99%
“…This paper is an outcome of a wider research program undertaken at Agris Sardegna between 2013 and 2016 for evaluating the impact of PTG on their ingestive behavior and milk production of dairy ewes ( 3 , 4 , 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%